The murine female intestinal microbiota does not shift throughout the estrous cycle. - Jessica G Wallace; Ryan H Potts; Jake C Szamosi; Michael G Surette; Deborah M Sloboda (PLoS ONE, 2018)
Pregnancy is accompanied by maternal physiological adaptations including metabolic, endocrine, immune, cardiovascular, skeletomuscular and neurological modifications that facilitate fetal and placental growth and development. Emerging evidence suggests that the maternal intestinal microbiota is modified over the course of healthy pregnancy. We have recently identified a maternal intestinal microbial shift within hours of conception; a shift that continued with advancing gestation. It is possible that maternal gut bacterial profiles might be associated with the known endocrine changes that accompany the female reproductive (estrous) cycle. Methods To determine whether the estrous cycle influenced the shifts in the maternal intestinal microbiota, time-matched fecal pellets were collected daily for 3 consecutive estrous cycles from individually housed, non-pregnant female C57BL/6J mice (n = 10) fed a control diet. Estrous stage was identified by cell type predominance in vaginal cytological samples. The corresponding fecal pellets for each estrous stage were processed for bacterial 16S rRNA sequencing of the variable 3 (V3) region. Results Estrous cycle stage accounted for a very small and not statistically significant proportion of the variation in the fecal microbiota according to PERMANOVA testing performed on Bray-Curtis dissimilarity scores. These values displayed no significant clustering of fecal microbial communities by estrous stage. Conclusion The estrous cycle does not result in any significant shift in the intestinal microbial community in the reproductively mature, regularly cycling female mouse.